2018
DOI: 10.1021/acs.nanolett.7b04421
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Mechanical Behavior of Nacre-Mimetic Graphene-Oxide and Silk Nanocomposites

Abstract: Biological materials have the ability to withstand extreme mechanical forces due to their unique multilevel hierarchical structure. Here, we fabricated a nacre-mimetic nanocomposite comprised of silk fibroin and graphene oxide that exhibits hybridized dynamic responses arising from alternating high-contrast mechanical properties of the components at the nanoscale. Dynamic mechanical behavior of these nanocomposites is assessed through a microscale ballistic characterization using a 7.6 μm diameter silica spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 49 publications
0
77
1
Order By: Relevance
“…In this regard, the fundamental studies of the mechanics of nanolaminates described in this paper provide key understandings of the pathways for their toughening and explain recent experimental findings hinting at the potential of 2D materials in transportation and ballistic-protection applications. 9 Indeed, the ultrathin GO-PVA structures reported here show significant failure resistance while preserving good stiffness and light weight. The GO monolayers are significantly toughened by atomically thin layers of PVA through controlled interfacial interactions: the microscale cracks are bridged by the PVA chains, which delay and shield crack growth through a hydrogen-bond-mediated network.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In this regard, the fundamental studies of the mechanics of nanolaminates described in this paper provide key understandings of the pathways for their toughening and explain recent experimental findings hinting at the potential of 2D materials in transportation and ballistic-protection applications. 9 Indeed, the ultrathin GO-PVA structures reported here show significant failure resistance while preserving good stiffness and light weight. The GO monolayers are significantly toughened by atomically thin layers of PVA through controlled interfacial interactions: the microscale cracks are bridged by the PVA chains, which delay and shield crack growth through a hydrogen-bond-mediated network.…”
Section: Resultsmentioning
confidence: 81%
“…For instance, it has been shown that graphene and graphene oxide-polymer systems have the potential to offer superior performance to Kevlar in body armor applications. [7][8][9] Likewise, graphene/Al 2 O 3 has been utilized as reinforcing components in lightweight aluminum composites. 10 Unfortunately, the presence of ''architectural defects'' such as voids and wrinkles found in previously produced 2D materials, in thin-film form, resulted in limited mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…55 In addition, the ratio between projectile radius and lm thickness is relatively small compared to standard thin lm LIPIT. 53,62,63 The small ratio in this work was purposely chosen to investigate and highlight the frictional effects in the thickness direction on the impact response of lms, similar to a previous experimental study on high strain rate deformation of layered nanocomposites using LIPIT. 52 This is because when the projectile radius is orders of magnitude larger than the lm thickness, the deformation in the thickness direction of the lm can be usually treated as uniform and the interlayer friction inside the lm would be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…GO with a higher specific surface area and abundant functional groups has wide applications in cell adhesion, reinforcing material and antibacterial activity [35,36]. GO can easily form hydrogen bonds with the hydrophilic amide groups in silk fibroin (SF) because GO contains lots of oxygen functional groups [37,38].…”
Section: Introductionmentioning
confidence: 99%